A New Platelet Aggregating Material (PAM) in an Experimentally Induced Rat Fibrosarcoma - Mohanty, D; Hilgard, P (Thrombosis and Haemostasis, 1984)
The present work concerns our studies to search for factor(s) which may influence the hemostatic process in or around metastasis of tumours. We studied the platelet aggregating property of a methyl cholanthrene induced experimental tumour. Platelet aggregating material was found to be different from the known aggregating agents like thrombin, ADP, collagen, thromboxane A2 and trypsin. It depends on a critical level of calcium for its action. PAM is a high molecular weight substance which contains sialic acid. It is trypsin and plasmin insensitive. The activity of this substance is not being destroyed by phospholipase-C. Metabolic study indicates that PAM acts by mitochondrial energy metabolic pathway of the platelets.
Keywords: Platelet aggregating material (PAM); Tumour extract; Inhibitors of PAM